Integrating Deep Learning to Foster Meaningful and Joyful Learning in Quranic Studies: A Merdeka Curriculum Framework - Paimin Paimin; Imam Syafi’i; Jaenullah Jaenullah (Assyfa Journal of Islamic Studies, 2026)
The implementation of the Merdeka Curriculum in Islamic education demands a pedagogical shift from rote memorization to profound conceptual understanding, yet many Quranic studies classrooms still struggle with disengagement and superficial learning. This study aims to analyze the integration of the Deep Learning approach—characterized by mindful, meaningful, and joyful learning—within the Al-Qur'an Hadith subject at Madrasah Tsanawiyah. Using a qualitative case study design, data were gathered through in-depth interviews, participant observation, and documentation at MTs Mathla’ul Anwar Landbaw. The findings reveal that instructional planning aligns with KMA No. 1503 of 2025, emphasizing a "curriculum of love" through teaching modules that prioritize student-centeredness. The execution of this framework utilizes discovery and problem-based learning models, successfully shifting the paradigm from teacher-centered to student-centered engagement. Evaluation results, encompassing diagnostic, formative, and summative assessments, demonstrate a significant improvement in student learning outcomes, with average scores rising from 70.09 to 76.34. This study concludes that the Deep Learning framework effectively fosters a more holistic and enjoyable educational environment, enabling students to internalize Quranic values more deeply while meeting the competency standards of the Merdeka Curriculum. These results imply that the synergy between mindful engagement and structured curriculum flexibility is essential for modernizing religious education in the digital era.